Study the effect of surface sealant on microleakage in class V cavities filled by different restorative materials - Saeed, Niaz H. Ghareeb H.; Mhammed, Gollshang Ahmad; Saeed, Hawzheen Masoud Mohamad (Sulaimani Journal for Pure and Applied Sciences, 2013)
The aim of this study was to evaluate the effect of unfilled resin sealant coating on marginal leakage in decreasing microleakage in class v cavities using PROMEDICA light cure Nano-ceramic composite and nono glass ionomer filling material (EQUIA system). Twenty extracted sound human upper premolars has been selected, Standardized class v cavity with butt-joint marginal configuration were prepared in the middle third of the buccal and palatal surfaces of the tooth. The teeth were randomly divided into four groups of five teeth. Cavities of group 1 were restored with nano composite only , group 2 were restored with nano composite coated with unfilled resin sealant,group3 were restored with light curing nano glass ionomer filing only, and group4 were restored with light curing nonoglass ionomer filing . After rinsing and drying one thin coat of unfilled resin sealant was applied and were light polymerized for 15 seconds. The procedures for dye penetration using Methylene Blue dye were followed and examined under stereomicroscope for evaluation. The data collected were analyzed statistically using paired t test. Nanocomposite recorded less microleakage than nanoglass ionomer cement at occlusal and cervical margins. Results showed that restorations were coated with resin sealant showed significantly less dye penetration in comparison with uncoated surfaces. For nanocomposite filling material p value= 0.002 while for nano glass ionomer filling material p value=0.0047. Though the coating of unfilled resin sealant did not completely eliminated microleakage, unfilled resin sealant was effective in reducing microleakage of the esthetic restorations in class V restorations.
Keywords: Microleakage; Nanocomposite; Nano glassionomers and unfilled resin sealant surface coating